Molecular analysis of Ulva compressa (Chlorophyta, Ulvales) reveals its morphological plasticity, distribution and potential invasiveness on German North Sea and Baltic Sea coasts. Issue 1 (2nd January 2019) - Steinhagen, S.; Weinberger, F.; Karez, R.
ABSTRACT: To resolve historical misinterpretations of species descriptions and to comprehend the morphological diversity together with the distribution of Ulva compressa Linnaeus in northern Germany, a morphological and molecular study was undertaken of recently collected specimens and herbarium vouchers. Phylogenetic analyses from sequences of the plastid encoded tuf A gene confirmed that U. compressa is abundant along the German Baltic Sea and North Sea coasts. We were able to genetically confirm the presence of U. compressa in the Baltic Sea below salinities of 15 PSU. However, we detected morphologies agreeing with the attached and branched tubular type material only in the North Sea, while U. compressa on Baltic Sea coasts indiscriminately exhibited a very distinct morphology of sheet-like thalli that were always unattached, with the exception of one collection site. Drifting forms were also frequently detected in the Wadden Sea, but not on the island of Helgoland. The tuf A sequences of attached and tubular forms of U. compressa from the German Wadden Sea were identical to the drifting sheets found in the Wadden and Baltic Seas and the sequence divergence was extremely small at ≤0.9%. The proliferating, blade-like thalli of U. compressa appear as a nuisance ecotype that is able to form massive accumulations associated with oxygen depletion. Mass accumulations were observed to cause severe damage and increased mortality of habitat forming Zostera and Ruppia populations.